2021
DOI: 10.29332/ijhs.v5n1.1082
|View full text |Cite
|
Sign up to set email alerts
|

Managing the penetrated traumatic spinal injury by an airgun shot: A case report from Dr. Soetomo Hospital, Surabaya, Indonesia

Abstract: Penetrated Traumatic Spinal Injury by Airgun Shot are rare events. As a result, handling this case is both, thrilling and challenging. We present a case of a penetrated traumatic spinal injury from an airgun, as well as a summary of the literature on how to treat them. A 9-year-old boy was taken to hospital after being shot in the right side of his front neck with an air rifle. The patient had been shot from a distance with an upfront direction. The patient had no breathing problem but complained of pain durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Study question was formed from the PICO. Authors used the following search keywords to search all trials registers and databases: ("Traumatic Brain Injury" OR "TBI" OR "Traumatic Head Injury" OR "Brain Injury") AND ("Deep vein thrombosis" OR "DVT") AND ("DVT Prophylaxis" OR "Thrombosis Prophylaxis") (Jani & Subagio, 2021;Komilova et al, 2021).…”
Section: Search Protocolmentioning
confidence: 99%
“…Study question was formed from the PICO. Authors used the following search keywords to search all trials registers and databases: ("Traumatic Brain Injury" OR "TBI" OR "Traumatic Head Injury" OR "Brain Injury") AND ("Deep vein thrombosis" OR "DVT") AND ("DVT Prophylaxis" OR "Thrombosis Prophylaxis") (Jani & Subagio, 2021;Komilova et al, 2021).…”
Section: Search Protocolmentioning
confidence: 99%
“…Whether human capital investment to promote industrial innovation effectively was also influenced by external environmental policies, and healthy development was crucial. The Porter hypothesis suggested that appropriate environmental regulation would promote technological innovation and force firms to invest more in research and development to improve their pollution control capabilities, thereby promoting healthy social development (Jani & Subagio, 2021;Kelsey et al, 1996;Mataram, 2020;Velázquez et al, 2021). Health, as a form of human capital of equal importance to educational human capital, was a prerequisite for the existence and effectiveness of human capital.…”
Section: Literature Reviewmentioning
confidence: 99%